Increasing enrollment in MacEwan University’s co-op program for marketing majors - Down, McKenna; Reid, Ashley; Lam, Mercedes; Berry, Denise (My University, 2024)
The study aimed to identify barriers to enrolling in the marketing cooperative education program at MacEwan University and to develop strategies that encourage higher enrollment among marketing majors. Research focused on understanding student perceptions and the effectiveness of current enrollment initiatives, including the primary reasons for their low participation. The research design targeted non-co-op Bachelor of Commerce marketing students, employing a probability sampling method to ensure a representative sample. Major findings indicate that a higher likelihood of recommending the co-op program correlates with better knowledge of program details, suggesting that increasing awareness could boost interest. However, the impact of current advertisements on program recommendation is low, indicating the need for improved marketing strategies. Students preferred receiving information through emails and in-class presentations, which are deemed most effective. Despite some support for mandatory work-integrated learning, there is ambivalence toward making the co-op program compulsory, signalling a need for further exploration. Based on these findings, the study recommends establishing partnerships with local businesses for part-time co-op placements to avoid extending graduation timelines. Additionally, it suggests integrating co-op program information and promotional activities into relevant courses to enhance visibility and stimulate student interest. Another recommendation is allowing students to count co-op placements as elective credits, aligning practical experience with academic and career goals.
Keywords: cooperative education; enrollment